“Statute on Siberian provincial administration” of 1822: the first experience of codification by Michael Speransky - I. A. Konovalov (Правоприменение)
The subject. The article examines the reform of local government in Siberia carried out by the outstanding Russian statesman and reformer M.M. Speransky in the first quarter of the 19th century. The purpose of the article is to confirm or disprove the hypothesis that the “Statute on Siberian provincial administration” of 1822 formed the organizational structure of state administration in Siberia for almost a century as well as basis for future codifications of Russian legislation that would carry out by M. Speransky. The methodological basis of the research is combination of objectivity, historicism and alternativeness, which presuppose an unbiased approach in the analysis of the historical problems and a critical attitude towards the sources. The main results, scope of application. The “Statute on Siberian provincial administration” of 1822 was the first systematization of local legislation in the history of Russia. The Statute became the first practical experience in the preparation of a code of laws for M.M. Speransky and his collaborators. The Statute was ahead of the subsequent imperial codification and incorporation of legislation carried out under his leadership. The Speransky’s reform in Siberia in 1822 determined the foundations of the administrative-territorial structure of the Trans-Ural region of the country, which corresponded to the needs of the time. The Statute of 1822 also legitimized the volost public administration of the Siberian state peasants, which was organized in the last quarter of the 18th century. This system of administration put the peasant self-government under more strict control by the district police authorities. Particular attention in the article is paid to the structure, nature and organizational and legal issues of the activities of local government in Siberia. Conclusions. The increased interest in the establishment and development of Siberian regional governance is associated not only with the desire of researchers to look deeper into the past, but also with practical needs. Today it is necessary to research the events and facts of the Siberian past in a new way so as not to repeat old myths and delusions and to prevent the emergence of new ones.